Hyperlipidemic mice as a model for a real‐time in vivo detection of atherosclerosis by gold nanorods‐based diffusion reflection technique. Issue 1 (11th October 2018) - Chakraborty, Ruchira; Ankri, Rinat; Leshem‐Lev, Dorit; Hochhauser, Edith; Kornowski, Ran; Motiei, Menachem; Lev, Eli I.; Fixler, Dror
Abstract : Atherosclerosis (AS), the leading cause of morbidity and mortality in cardiovascular disease, needs an early detection for treatment and prevention of fatal events. Here, for the first time, we applied gold nanorods (GNRs)‐assisted diffusion reflection (DR), a noninvasive technique for in vivo detection of AS in a high‐fat‐diet‐induced c57bl mouse model, which resembles the manifestation of AS in humans. DR simply detects the change in light reflection profile of tissue due to the accumulation of GNRs in the AS plaques and enables clear detection of AS lesions in carotid and femoral arteries of these hyperlipidemic mice. After 24 hours post‐GNRs injection, DR showed the highest efficiency of AS detection. Moreover, the sensitivity of the DR method is much higher than computed tomography (CT) and is comparable to ex vivo high‐resolution CT. Our results strongly suggest that the DR method can detect early atherosclerotic lesions in a sensitive and specific manner. Abstract : Our gold nanorods‐based diffusion reflection method, a noninvasive technique, detects early stages of atherosclerosis in a hyperlipidemic mice model, with high specificity and selectivity.